Menthol and Menthone Associated with Acetylsalicylic Acid and Their Relation to the Hepatic Fibrosis in Schistosoma mansoni Infected Mice - Feitosa, Karina A. (Front Pharmacol, 2018)
Schistosomiasis is an important parasitic disease caused by Schistosoma mansoni, an intravascular trematode. Schistosomiasis treatment is limited to just one drug, Praziquantel (PZQ). Thus, studies on new antischistosomal compounds are of fundamental importance to disease control. Here we report on the effects of Mentha piperita L. compounds – menthol and menthone – in association with acetylsalicylic acid (ASA) in the regulation of hepatic fibrosis caused by schistosomiasis granulomas. Six different groups of Swiss rats were infected with 80 cercariae. Two groups received only menthol and menthol treatment at different concentrations (30 and 50 mg/kg); two groups received treatment with the same concentration of menthol and menthol, but associated the ASA. All groups received treatment for 14 consecutive days from the 35 days after the parasitic infection. In addition, three other groups were used: uninfected and untreated group, infected and untreated group and infected group treated with the commercial drug (single dose). Parasitological, cytological and histological analyses were performed. Results showed a significant reduction on the number of eosinophils found in the peritoneal cavity lavage (LPC) in all treated groups and on the number of eosinophils found in the blood of PZQ treated group, in the blood of the group treated with 30 mg/kg of Mentaliv(®) and in the blood of group treated with 50 mg/kg Mentaliv(®) + ASA when compared to the infected group. All treated groups presented a reduction in the parasite load, represented by the number of S. mansoni eggs, in the experimental group treated with 30 mg/kg of menthol and menthone a 62.80% reduction was observed and in the experimental group treated with 50 mg/kg of menthol and menthone + ASA a reduction of 64.21% was observed. In the liver histological analysis we observed that all Mentaliv(®) treated groups expressed a unique cytological profile, with diffused cells through the granuloma. In the experimental group treated with 50 mg/kg of Mentaliv(®) + ASA it was possible to observe the formation of type III collagen fibers, a typical wound healing characteristic. Our data strongly suggest that both the hepatic fibrosis and the inflammatory process were regulated through the schistosomiasis granulomatous process after treatment with menthol and menthone associated with ASA.